Age-specific anti-Mullerian hormone (AMH) levels poorly affects cumulative live birth rate after intra-uterine insemination - Moreau, Jessika (Eur J Obstet Gynecol Reprod Biol X, 2019)
OBJECTIVE: To evaluate the impact of age-specific anti-Mullerian (AMH) levels on the cumulative live birth rate after 4 intra uterine inseminations (IUI). STUDY DESIGN: The retrospective study study involved 509 couples who underwent their first IUI between January 2011 and July 2017 in the Toulouse University Hospital. All IUI were performed after an ovarian stimulation combining recombinant FSH and GnRH antagonist. The main measure outcome was the cumulative live birth rate (LBR) defined as the number of deliveries with at least one live birth resulting from a maximum of 4 IUI attempts. RESULTS: When compared to normal or high levels, low age-specific AMH (<25th of the AMH in each age group) was associated to a non-significant lower live birth rate (31%, 38% and 42% respectively for low, normal and high age-specific groups; P = 0.170) and non-significant higher miscarriage rate (26%; 19% and 14% respectively for low, normal and high age-specific groups; P = 0.209). However, it must be pointed out that in low age-specific AMH the initial FSH doses used for stimulation were higher than in the other groups. CONCLUSION: This study shows that the age-specific levels of AMH have only a slight effect on IUI outcome when adapting the stimulation protocols to their level.